Resin composition and elastomer material made from said resin composition
By adding polyacrylate resin and silicate particles to the resin composition, the problem of insufficient biocompatibility and anti-hemocoagulation properties of polymer materials is solved, and a resin composition with high mechanical strength and anti-hemocoagulation is achieved, which is suitable for medical devices.
Patent Information
- Application Number
- JP2020096690
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-06-03
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2040-06-03
Smart Images

Figure 0007623638000006 
Figure 0007623638000007 
Figure 0007623638000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition which has excellent mechanical properties such as flexibility, extensibility and toughness and can be suitably used as an elastomer material with excellent antithrombotic properties, and to an elastomer material made of said resin composition. [Background technology]
[0002] When artificially synthesized polymer materials are used in medical devices that require biocompatibility, it is desirable to prevent adhesion, activation, and coagulation of biological tissue components, including platelets, to the surface of the polymer material, which occurs when the polymer material surface comes into contact with biological components such as blood, as the biological tissue recognizes the polymer material as a foreign body.
[0003] For example, in medical devices used in contact with blood, such as catheters, artificial blood vessels, and blood bags, antithrombotic properties to prevent blood clotting are essential, and non-patent document 1 discloses poly(2-methoxyethyl acrylate) (PMEA) as a polymer material that exhibits such antithrombotic properties.
[0004] However, Patent Document 1 merely teaches that such a polymer material having a specific molecular structure with antithrombogenicity can be used as a coating agent that forms an antithrombogenic film.
[0005] In other words, antithrombotic polymer materials such as PMEA have poor mechanical strength, and it is difficult to obtain elastomers or molded bodies made of a single polymer material. Therefore, their use is limited to their use as coating agents. Depending on the type of substrate material, adhesion between the substrate and the coating film can be an issue, and loss of antithrombotic properties is unavoidable due to peeling of the coating film. In addition, there are limitations on the shape of the substrate (molded body) that can be used.
[0006] On the other hand, Non-Patent Document 2 shows that a composite elastomer material containing an acrylic polymer having a specific molecular structure and silica fine particles has transparency and excellent toughness, and is expected to be used in medical devices that require transparency and flexibility, but does not show the presence or absence of biocompatibility, including antithrombogenicity. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] M. Tanaka, et al, Biomaterials 2000, 21, 1471-1481. [Non-Patent Document 2] Y.Takeoka, et al., ACS Mater. Lett.2020, 2, 325-330. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a resin composition which has excellent mechanical properties, particularly flexibility, extensibility and toughness, and can be suitably used as an elastomer material having excellent antithrombogenicity. [Means for solving the problem]
[0009] The present inventors have discovered that the above object is to provide a resin composition containing a polyacrylate resin and silica particles, The polyacrylate resin comprises at least The following general formula (1): [ka] [In formula (1), R 0 represents a hydrogen atom, a methyl group, or an ethyl group; R 1 represents a hydrogen atom or a methyl group; and n represents an integer of 1 to 9. The present invention has been arrived at by finding that this can be achieved by the above-mentioned resin composition, which is characterized in that it contains the above-mentioned monomer unit and the content of the silica particles is in the range of 9 to 50 volume % of the entire resin composition. Effect of the Invention
[0010] The present invention provides a novel resin composition. The resin composition of the present invention is particularly suitable as an elastomeric material. The elastomer material made of the resin composition of the present invention is excellent in mechanical properties such as flexibility, extensibility and toughness, and is also excellent in antithrombogenicity. [Brief description of the drawings]
[0011] [Figure 1] 4 is a stress / strain curve of the resin composition obtained in Example 1. [Diagram 2] 4 is a stress / strain curve of the resin composition obtained in Example 2. [Diagram 3] 4 is a stress / strain curve of the resin composition obtained in Example 3. [Figure 4] 4 is a stress / strain curve of the resin composition obtained in Example 4. [Diagram 5] 4 is a stress / strain curve of the resin composition obtained in Comparative Example 1. [Figure 6] 4 is a stress / strain curve of the resin composition obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below. The resin composition of the present invention contains at least a polyacrylate resin and silica particles.
[0013] First, the polyacrylate resin contained in the resin composition will be described. The polyacrylate resin must contain, as a monomer unit, an acrylate monomer (A) represented by the following general formula (1). [ka]
[0014] In formula (1), R 0 R represents a hydrogen atom, a methyl group, or an ethyl group, preferably a hydrogen atom or a methyl group, more preferably a methyl group. 1 represents a hydrogen atom or a methyl group, and preferably a hydrogen atom. n represents an integer of 1 to 9, preferably 1 to 5, more preferably 1 to 3, and even more preferably 1 to 2.
[0015] The acrylate monomer (A) represented by the above general formula (1) can be converted into an acrylate resin by thermal polymerization or photopolymerization.
[0016] In the above general formula (1), R 1 In the case of acrylate monomers where the aryl group is a hydrogen atom, photopolymerization proceeds faster, so polyacrylate resins can be produced in a short time. The use of photopolymerization in this way is beneficial in that it makes it easy to obtain elastomers of various shapes, and also makes it easier to mold using a stereolithography 3D printer or to apply photocurable coatings.
[0017] Specific examples of the acrylate monomer represented by general formula (1) include, for example, 2-methoxyethyl acrylate, 2-methoxyethyl methacrylate, diethylene glycol monomethyl ether acrylate, diethylene glycol monomethyl ether methacrylate, triethylene glycol monomethyl ether acrylate, triethylene glycol monomethyl ether methacrylate, polyethylene glycol monomethyl ether methacrylate (number average molecular weight 300), and polyethylene glycol monomethyl ether methacrylate (number average molecular weight 1100). From the viewpoint of dispersibility of silica particles and physical properties of the resulting resin composition, preferred are 2-methoxyethyl acrylate, 2-methoxyethyl methacrylate, diethylene glycol monomethyl ether acrylate, diethylene glycol monomethyl ether methacrylate, triethylene glycol monomethyl ether acrylate, and triethylene glycol monomethyl ether methacrylate, more preferably 2-methoxyethyl acrylate, diethylene glycol monomethyl ether acrylate, diethylene glycol monomethyl ether methacrylate, and triethylene glycol monomethyl ether methacrylate, and even more preferably 2-methoxyethyl acrylate and diethylene glycol monomethyl ether methacrylate. The acrylate monomer represented by the general formula (1) may be used alone or in combination of two or more kinds, so long as the effects of the present invention are not impaired.
[0018] Among the acrylate monomers represented by general formula (1), specific examples of photopolymerizable monomers include, for example, 2-methoxyethyl acrylate, diethylene glycol monomethyl ether acrylate, and triethylene glycol monomethyl ether acrylate. From the viewpoint of the dispersibility of silica particles and the physical properties of the resulting resin composition, 2-methoxyethyl acrylate, diethylene glycol monomethyl ether acrylate, and triethylene glycol monomethyl ether acrylate are preferred, more preferably 2-methoxyethyl acrylate, diethylene glycol monomethyl ether acrylate, and even more preferably 2-methoxyethyl acrylate. These acrylate monomers may be used alone or in combination as long as they do not impair the effects of the present invention.
[0019] The polyacrylate resin contained in the resin composition of the present invention may use a difunctional or higher acrylate monomer as a crosslinking agent as a monomer unit. For example, examples of the difunctional acrylate monomer include ethylene glycol diacrylate, EO modified bisphenol A diacrylate, 1,4-butanediol diacrylate, diethylene glycol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, trimethylolpropane diacrylate, and polyethylene glycol diacrylate (polyethylene glycol chain molecular weight 100 to 10000), examples of the trifunctional acrylate monomer include trimethylolpropane triacrylate and pentaerythritol triacrylate, and examples of the tetrafunctional or higher acrylate monomer include pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, tripentaerythritol octaacrylate, tetrapentaerythritol decaacrylate, and pentapentaerythritol dodecaacrylate. In view of the dispersibility of silica particles and the physical properties of the resulting resin composition, a bifunctional acrylate monomer is preferred, preferably ethylene glycol diacrylate, 1,4-butanediol diacrylate, or diethylene glycol diacrylate, more preferably diethylene glycol diacrylate. The bifunctional or higher acrylates may be used alone or in combination as long as they do not impair the effects of the present invention.
[0020] In the above general formula (1), R 1 When an acrylate monomer in which is a hydrogen atom is used, the resulting acrylate resin has a glass transition point significantly below zero degrees and is highly viscous, making it difficult to handle. For this reason, it is preferable to use the above-mentioned di- or higher-functional acrylate monomer as the crosslinking agent.
[0021] The di- or higher functional acrylate monomer may be contained in the resin composition in an amount of less than 5 mol%, preferably less than 2 mol%, more preferably less than 1 mol%, and even more preferably less than 0.6 mol%, based on 100 mol% of all monomer units. If the di- or higher functional acrylates are contained in an amount of 5 mol% or more, the tensile elongation at break of the elastomer material is significantly reduced.
[0022] The polyacrylate resin contained in the resin composition of the present invention may contain a silane coupling agent represented by the following general formula (2) as a monomer unit. [ka]
[0023] In formula (2), R 2 R represents a hydrogen atom or a methyl group, preferably a methyl group. 3 R represents a methoxy or ethoxy group, preferably a methoxy group. 4 represents a methyl group, a methoxy group or an ethoxy group, preferably a methyl group or a methoxy group.
[0024] Specific examples of the silane coupling agent represented by general formula (2) include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane. In view of the high improvement of mechanical properties, 3-methacryloxypropylmethyldimethoxysilane or 3-methacryloxypropyltrimethoxysilane is preferred, and 3-methacryloxypropyltrimethoxysilane is more preferred. The silane coupling agent represented by general formula (2) may be used alone or in combination as long as it does not impair the effects of the present invention.
[0025] When the resin composition of the present invention is prepared by photopolymerization, the silane coupling agent represented by the general formula (2) is R 2However, it is preferable to use a hydrogen atom.
[0026] When the silane coupling agent is used, it is sufficient that the silane coupling agent is contained in the resin composition in an amount such that the surface coverage ratio of the silane coupling agent to the silica particles is in the range of 0.005 to 0.080, preferably 0.006 to 0.076, more preferably 0.007 to 0.080, and even more preferably 0.010 to 0.075.
[0027] Here, the surface coverage ratio is a value obtained by the following formula. [Surface coverage ratio] = [Amount of silane coupling agent contained in resin composition (g)] × [Minimum coverage area of silane coupling agent (m 2 / g)]÷[surface area of silica particles contained in the resin composition (m 2 )
[0028] "Minimum coverage area of silane coupling agent (m 2 "(g)" refers to the area that the silane coupling agent covers on the surface of a material such as silica when 1 g of the silane coupling agent reacts or adsorbs on the surface, and the minimum coverage area of each silane coupling agent can usually be calculated as follows. That is, assuming that Si(O)3 obtained by hydrolysis of trialkoxysilane is one Si atom in a sphere with a radius of 2.10 Å and three O atoms in a sphere with a radius of 1.52 Å, the Si-O bond distance is 1.51 Å, and the tetrahedral angle is 109.5°, and further assuming that all three O atoms in the model react with the silanol groups on the silica surface, the minimum circular area that can be covered by the three O atoms is calculated. As a result, the coverage area per molecule is 1.3 x 10 -19 m 2 / numerator, with Avogadro's constant 6.0 × 10 23 Multiplying by molecules / mole converts to per mole: 7.8 x 10 4 m 2 The minimum coverage area of each coupling agent is the value obtained by dividing the coverage area per mole by the molecular weight of each silane coupling agent.
[0029] Commercially available silane coupling agents have their characteristic values indicated and described, and in the present invention, the values indicated and described by the distributor may be used.
[0030] In addition, the surface area of silica particles (m 2 ) is the sum of the surface area (m2) of silica particles calculated from the average particle size. 2 ) × Amount of silica particles added (g) ÷ Density of silica particles (g / cm 3 ) / "Volume of silica particles calculated from the average particle size (m 3 ) is the value obtained by calculating
[0031] The polyacrylate resin in the resin composition of the present invention may be combined with a different acrylate monomer in addition to the acrylate monomer (A) represented by general formula (1), and may be combined with a different silane coupling agent in addition to the silane coupling agent (B) represented by general formula (2), as long as the effects of the present invention are not impaired.
[0032] Next, the silica particles used in the present invention will be described. In the present invention, the silica particles are an important component for enabling the resin composition of the present invention to be used as an elastomer material and for improving the toughness of the resin composition, since without the silica particles, the material would be brittle and unable to withstand large deformations. The shape of the silica particles used in the present invention is not particularly limited as long as it does not impair the effects of the present invention, but it is preferably "spherical" from the viewpoint of dispersibility in a dispersion medium. In addition, the use of spherical silica makes it possible to obtain a transparent elastomer. In the present invention, the term "spherical" refers to a true sphere, an approximately sphere, or a spheroid, excluding rod-like or plate-like ones, and may have an uneven surface. "Spherical silica particles" are silica particles having such a "spherical" shape.
[0033] As such spherical silica particles, known ones can be used, such as powdered spherical silica particles and colloidal silica (silica sol), and various known ones having different average particle sizes are known and commercially available.
[0034] The silica particles used in the present invention have an average particle size of less than 10 μm, preferably less than 5 μm, more preferably less than 1 μm, even more preferably less than 500 nm, and most preferably less than 200 nm. In the present invention, the average particle size is represented by the mode diameter measured by a centrifugal sedimentation type particle size distribution measuring device.
[0035] The content of the silica particles is 9 to 50% by volume of the entire resin composition, preferably 12 to 48% by volume, more preferably 15 to 45% by volume, even more preferably 18 to 45% by volume, and most preferably 10 to 40% by volume. The lower the content of the silica particles, the smaller the reinforcing effect of the polymer material due to the silica particle filling, resulting in an elastomer material with inferior tensile modulus and tensile breaking stress. If the content of the granular silica particles is too high, it becomes difficult to uniformly disperse the silica particles in the acrylate monomer.
[0036] The volume percent (V(%)) of the resin composition, which indicates the content of silica particles in the present invention, is Density of the resin composition (d(g / m 3 ) and the weight retention rate (%) calculated from the weight (m(g)) residual after heating at 500°C for 1 hour, according to the following formula: V(%)=[density of resin composition (g / cm 3 )] × [Weight retention after heating at 500°C for 1 hour (%)] ÷ [Density of spherical silica particles (2.2 g / cm 3 )]
[0037] The resin composition of the present invention can be obtained by polymerizing a dispersion containing at least the acrylate monomer (A) represented by general formula (1) and silica particles.
[0038] As the polymerization method, thermal polymerization using a thermal polymerization initiator, photopolymerization using a photopolymerization initiator accompanied by irradiation with active energy rays such as ultraviolet rays, etc. can be used, and other polymerization methods may also be used as long as they do not impair the effects of the present invention.
[0039] <Thermal polymerization initiator> The thermal polymerization initiator is not particularly limited in structure as long as it generates radicals by heating and is used to initiate polymerization of the polymerizable functional group in the resin composition. For example, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), 2,2'-azobis[2-(2-imidazolin-2-yl)propane], Benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxy 2-ethylhexanoate, t-butyl peroxy neodecanoate, t-butyl peroxy pivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, diacetyl peroxide, etc. are listed, and 2,2'-azoisobutyronitrile (AIBN) is preferred in terms of reactivity. The amount of the thermal polymerization initiator added is 0.001 parts by mass or more, preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and 7 parts by mass or less, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, based on 100 parts by weight of the acrylic monomer component. These thermal polymerization initiators may be used alone or in combination of two or more kinds.
[0040] <Photopolymerization initiator> The photopolymerization initiator is not particularly limited in structure as long as it is used to generate radicals by ultraviolet irradiation and initiate polymerization of the polymerizable functional group in the resin composition. As the photopolymerization initiator, it is preferable to use an initiator having a light absorption wavelength of 360 nm to 470 nm, and examples thereof include acylphosphine oxide-based, α-aminoacetophenone-based, benzophenone-based, camphorquinone-based and thioxanthone-based initiators. By using these initiators, polymerization efficiently progresses to the inside of the resin composition, improving the mechanical strength and reducing the amount of residual components such as initiators and monomers.Examples of photopolymerization initiators include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, ethyl (2,4,6-trimethylbenzoyl) phenylphosphine oxide, bis (2,4,6-trimethylbenzoyl) phenylphosphine oxide, 2,4-diethylthioxanthone, 2-isopropylthioxanthone, oligo (2-hydroxy-2-methyl-1- (4- (1-methylvinyl) phenyl) propanone), 2-benzyl-2-dimethylamino-1- (4-morpholinophenyl) -butanone-1 ,2-Dimethylamino-2-(4-methyl-benzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, 2-[4-(methylthiobenzoyl)]-2-(4-morpholinyl)propane, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, 1-hydroxycyclohexyl phenyl ketone, [4-[4-methylphenyl]thio]phenyl]phenylmethanone, ethyl 4-(dimethylamino)benzoate, 1-[4-(2 -hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 4,4'-bis-(dimethylamino)benzophenone, 4,4'-diethylaminobenzophenone, 1-[4-(4-benzoylphenylsulfanyl)phenyl]-2-methyl-2-[(4-methylphenyl)sulfonyl]propan-1-one, (methylimino)diethane-2,1-diyl(4-dimethylamibenzoate), lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate, bis(4-methoxybenzo In view of reactivity, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, ethyl(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate, and bis(4-methoxybenzoyl)diethylgermanium are preferred, and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide is more preferred.The amount of the photopolymerization initiator added is 0.001 parts by mass or more, preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and 7 parts by mass or less, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, relative to 100 parts by weight of the acrylic monomer component. These photopolymerization initiators may be used alone or in combination of two or more kinds.
[0041] In addition, a chain transfer agent may be used in the polymerization reaction. Examples of the chain transfer agent include mercaptocarboxylic acids such as mercaptoacetic acid and 3-mercaptopropionic acid; mercaptocarboxylic acid esters such as methyl mercaptoacetate, methyl 3-mercaptopropionate, 2-ethylhexyl 3-mercaptopropionate, n-octyl 3-mercaptopropionate, methoxybutyl 3-mercaptopropionate, stearyl 3-mercaptopropionate, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), and dipentaerythritol hexakis(3-mercaptopropionate); ethyl mercaptan, t-butyl mercaptan, n-dodecyl mercaptan, and the like. Examples of the chain transfer agent include alkyl mercaptans such as mercaptan and 1,2-dimercaptoethane; mercaptoalcohols such as 2-mercaptoethanol and 4-mercapto-1-butanol; aromatic mercaptans such as benzenethiol, m-toluenethiol, p-toluenethiol, and 2-naphthalenethiol; mercaptoisocyanurates such as tris[(3-mercaptopropionyloxy)-ethyl]isocyanurate; disulfides such as 2-hydroxyethyl disulfide and tetraethyl thiuram disulfide; dithiocarbamates such as benzyl diethyl dithiocarbamate; monomer dimers such as α-methylstyrene dimer; and alkyl halides such as carbon tetrabromide. The amount of the chain transfer agent to be added is 0.001 parts by mass or more, preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and 7 parts by mass or less, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, based on 100 parts by weight of the acrylic monomer component. These may be used alone or in combination of two or more.
[0042] When using powdered silica particles as the silica particles, it is preferable to first disperse the silica particles in the acrylate monomer (A). The method of dispersing the silica particles in the acrylate monomer (A) is not particularly limited as long as it does not impair the effects of the present invention, but the method of ultrasonic treatment is preferable because of its high dispersion effect.
[0043] When colloidal silica (silica sol) is used as silica particles, it is preferable to use the organic solvent mixed with the acrylic monomer component, for example, alcohols, ketones, esters, glycol ethers.From the viewpoint of ease of solvent removal, it is preferable to use alcohol-based organic solvents such as methanol, ethanol, isopropyl alcohol, butyl alcohol, n-propyl alcohol, and ketone-based organic solvents such as methyl ethyl ketone and methyl isobutyl ketone, and specifically, it is preferable to use colloidal silica (silica sol) dispersed in methanol, isopropyl alcohol, or methyl ethyl ketone.
[0044] A preferred method for producing the resin composition of the present invention is to prepare a dispersion by mixing and dispersing a predetermined amount of silica particles in an acrylate monomer (A) represented by general formula (1), and then mixing and dispersing a polymerization initiator, other acrylic monomers, and desired additives into the dispersion as necessary, and polymerizing the obtained dispersion. The desired additives include, for example, plasticizers, surfactants, dispersants, antioxidants, ultraviolet absorbers, fluorescent agents, crosslinking agents, organic solvents, etc., and can be added and used according to the purpose within a range that does not impair the effects of the present invention.
[0045] The resin composition of the present invention can be suitably used as an elastomer material. The elastomer material made of the resin composition of the present invention is excellent in reinforcing properties, mechanical properties (tensile modulus of elasticity, tensile stress at break, tensile strain at break, tensile energy at break, etc.) and antithrombogenicity.
[0046] The elastomer material made of the resin composition of the present invention has a tensile modulus of elasticity of 350 kPa or more, preferably 400 kPa or more, and more preferably 450 kPa or more.
[0047] The elastomer material made of the resin composition of the present invention has a tensile breaking strain of 250% or more, preferably 350% or more.
[0048] The elastomer material made of the resin composition of the present invention has a tensile breaking stress of 600 kPa or more, preferably 1000 kPa or more, and more preferably 1500 kPa or more.
[0049] The elastomer material made of the resin composition of the present invention has a tensile energy at break of 800 kJ / m 3 More than 1500kJ / m 3 More preferably, 2000 kJ / m 3 The above.
[0050] The elastomer material made of the resin composition of the present invention has excellent antithrombotic properties in addition to the above mechanical properties, and therefore can be suitably used as a biocompatible material.
[0051] It is known that when blood or the like comes into contact with the surface of a material with low biocompatibility, platelets adhere to the surface of the material, whereas platelet adhesion is suppressed on the surface of a material with high biocompatibility, and the latter is considered to be a material with excellent antithrombogenicity. When proteins in biological tissues are adsorbed or denatured on the surface of various materials, platelets are adsorbed to the adsorbed or denatured proteins and become denatured, causing thrombus, etc., so the method of evaluating platelet adhesion is commonly used as a means of evaluating the biocompatibility of various material surfaces.
[0052] In the present invention, platelet adhesion was evaluated using a platelet concentration of 1.75×10 7 A platelet suspension of 100 cells / mL was dropped at 200 μL onto a sheet sample with a side length of 8 mm, and the number of platelets adhering to the sample surface after leaving it to stand at 37°C for 1 hour was compared.
[0053] The elastomer material made of the resin composition of the present invention has a platelet adhesion number (cells / cm) of 1.0 to 1.0 mm. 2 )] / [Number of platelets attached to PET resin (cells / cm 2 )] (hereinafter referred to as "platelet adhesive index") is 0.5 or less, preferably 0.4 or less, and more preferably 0.3 or less. [The platelet adhesion number (cells / cm 2 )] is the control value in this evaluation of platelet adhesion. [Industrial Applicability]
[0054] The resin composition of the present invention can be suitably used as an elastomer material and can be used for industrial component applications such as display members, glass interlayers, coating agents, pressure sensitive adhesives, adhesives, vibration damping materials, 3D printer materials, and self-repairing materials, as well as medical devices that require antithrombotic properties. In particular, it is expected to be used in medical devices that require antithrombotic properties, such as catheters, artificial blood vessels, and blood bags. EXAMPLES
[0055] The present invention will be described below using specific examples. However, the present invention should not be interpreted as being limited to these examples. It should be understood that the present invention includes all technical ideas and specific embodiments that a person skilled in the art who comes into contact with the concept of the present invention would conceive and consider to be feasible.
[0056] The measurement and evaluation methods for each characteristic value in the examples are as follows. (1) Volume percent of spherical silica particles in the resin composition The density of the resin composition (d(g / m)) was measured using a dry density meter (AccPyc1330) manufactured by Shimadzu Corporation. 3 )) and the weight retention rate (%) obtained from the weight (m(g)) residual after heating at 500°C for 1 hour measured using a Shimadzu Corporation differential thermal and thermogravimetry simultaneous analyzer (DTG-60) was used to calculate the volume percent (V(%)) of the spherical silica particles according to the following formula. V(%)=[density of resin composition (g / cm 3 )] × [Weight retention after heating at 500°C for 1 hour (%)] ÷ [Density of spherical silica particles (2.2 g / cm 3 )]
[0057] (2) Mechanical properties In accordance with JIS K7161-2, a stress / strain curve was obtained, and the tensile modulus, tensile breaking stress, tensile breaking strain, and tensile energy at break were measured at 0.05-0.025% elongation.
[0058] For the tensile test, a No. 7 dumbbell test piece (JISK7161-2) was prepared from a 1 mm thick sheet of the resin composition using a punching die. Using a tensile tester (EZ-LX) manufactured by Shimadzu Corporation, the test was performed under standard conditions (temperature 23±2°C, in air, humidity (50±10%)) at a tensile speed of 0.1 mm / min up to a strain of 0.3%, and at a tensile speed of 50 mm / min beyond the strain of 0.3%.
[0059] (2-1) Tensile modulus at 0.05-0.25% elongation The tensile modulus at 0.05-0.25% elongation was evaluated according to the following criteria. ○: 350kPa or less tensile modulus ×: Tensile modulus <350kPa
[0060] The reason why the tensile modulus of elasticity is set at 350 kPa as the cutoff point for evaluation is that the tackiness of the resin composition decreases, making it easier to handle.
[0061] (2-2) Tensile breaking stress The tensile breaking stress was evaluated according to the following criteria. ○: 600kPa or less tensile breaking stress ×: Tensile breaking stress <600kPa
[0062] The reason for setting the evaluation limit at 600 kPa for the tensile breaking stress is to ensure durability against momentary external forces.
[0063] (2-3) Tensile breaking strain The tensile breaking strain was evaluated according to the following criteria. ○: 250% or less tensile breaking strain ×: Tensile breaking strain <250%
[0064] The reason why the tensile breaking strain is set at 250% as the evaluation boundary is to ensure the elasticity of the elastomer material.
[0065] (2-4) Tensile energy The tensile energy at break was evaluated according to the following criteria. ○: Tensile energy at break ≧800kJ / m 3 ×:800kJ / m 3 >Tensile energy at break
[0066] Tensile energy: 800kJ / m 3 The reason for setting this as the evaluation boundary is to ensure toughness to withstand large deformation.
[0067] (3) Platelet adhesiveness A solution made by mixing human whole blood and 3.2% sodium citrate buffer in a ratio of 9:1 was centrifuged (200 g, 5 minutes) using a Kubota high-speed refrigerated centrifuge (6200), and the supernatant was collected and used as platelet rich plasma (PRP). A portion of the PRP was separated, and the remaining PRP was further centrifuged (1500 g, 10 minutes), and the supernatant was similarly collected to obtain platelet poor plasma (PPP). The PRP was diluted 100-fold with phosphate-buffered saline (PBS) and the platelet count of the PRP was counted under an optical microscope. The platelet concentration was 1.75 × 10 7 A platelet suspension was prepared by diluting PRP with PPP to obtain a platelet concentration of 100 cells / mL.
[0068] A sheet of the resin composition of each Example and Comparative Example cut into a square with sides of 8 mm was placed in an Eppendorf Cell Imaging cover glass (8 chambers), and 200 μL of the prepared platelet suspension was dropped onto each sheet, followed by leaving it to stand at 37°C for 1 hour. Thereafter, the platelet suspension was absorbed, the sheet was washed twice with 400 μL of PBS, 200 μL of 1% glutaraldehyde in PBS was dropped onto it, and the obtained sheet was left to stand at 37° C. for 2 hours. Thereafter, the 1% glutaraldehyde PBS solution was absorbed, and the sheet was washed twice with 300 μL of PBS, once with 300 μL of a 1:1 solution of PBS:ultrapure water, and once with 300 μL of ultrapure water, and then air-dried at 37°C. The dried sheets were osmium coated using an osmium plasma coater (OPC60A) manufactured by Filgen, and the number of platelets attached to the sheet surface was counted using an FE-SEM (JSM-7500FA) manufactured by JEOL Ltd. Measurements were performed in five fields of view for each sheet (N=3), and the number of platelets attached in each field of view was converted to the number of platelets per unit area to calculate the average value. The number of platelets adhering to the surface of each sheet and the number of platelets adhering to the surface of a PET film (control) (Emblett (registered trademark) S-50 (manufactured by Unitika Ltd.)) were used as the standard. [Platelet adhesion index] = [Number of platelets attached to elastomer material made of resin composition (cells / cm 2 )] / [Number of platelets attached to PET (cells / cm 2 )] asked for.
[0069] PET film (control) [Number of platelets attached to PET (cells / cm 2 )] value is 8.4×10 4 (cells / cm 2 ) was.
[0070] Platelet adhesion was evaluated according to the following criteria. 〇: Platelet adhesive index ≦0.5 ×:0.5<Platelet adhesive index
[0071] The platelet adhesiveness index value of 0.5 was set as the cutoff point for evaluation because it shows a strong tendency to suppress thrombus formation. The lower the number of adherent platelets, the better the antithrombotic properties, so there is no particular lower limit for the platelet adhesiveness index.
[0072] Example 1 2712 parts by mass of diethylene glycol monomethyl ether methacrylate (MEO2MA, manufactured by Aldrich Co., Ltd.) and 3288 parts by mass of spherical silica particles having an average particle size of 110 nm (Silbol 110, manufactured by Fuji Chemical Co., Ltd.) were placed in a test tube and dispersed at 5°C for 10 minutes using an ultrasonic homogenizer (UP200St, manufactured by Hielscher Co., Ltd.). As a polymerization initiator, 3.55 parts by mass of 2,2'-azobisisobutyronitrile (manufactured by Kanto Chemical Co., Ltd.) was added and mixed. The obtained dispersion was then poured into a 1 mm thick mold sandwiched between two glass plates with FEP (copolymer of tetrafluoroethylene and hexafluoropropylene) sheets attached, and heated in an oven at 70°C for 15 hours to obtain a 1 mm thick sheet.
[0073] The volume percentage of the spherical silica particles in the resin composition of the obtained sheet was 39%.
[0074] The resulting sheet, 1 mm thick, was used to carry out a tensile test, and the resulting stress / strain curve is shown in Figure 1. The measurement and evaluation results of the mechanical properties (tensile modulus, tensile breaking stress, tensile breaking strain, and tensile energy at break) obtained from the stress / strain curve are summarized in Table 1 below.
[0075] The platelet adhesion measurement and evaluation results are also shown in Table 1.
[0076] Example 2 2,070 parts by mass of 2-methoxyethyl acrylate (MEA, manufactured by Tokyo Chemical Industry Co., Ltd.), diethylene glycol diacrylate (DEGDA, manufactured by Tokyo Chemical Industry Co., Ltd.), and 2,477 parts by mass of spherical silica particles having an average particle size of 110 nm (Silbol 110, manufactured by Fuji Chemical Industry Co., Ltd.) were placed in a test tube and dispersed at 5° C. for 10 minutes using an ultrasonic homogenizer (UP200St, manufactured by Hielcher). As a polymerization initiator, 2.69 parts by mass of 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (manufactured by Aldrich Co.) was added and mixed. The resulting dispersion was then poured into a 1 mm thick mold sandwiched between two glass plates with FEP sheets attached, and irradiated with ultraviolet light (UVF-204S, manufactured by Minaeshi Electric Co., Ltd.) at 365 nm and 10 mW / cm. 2 The film was then irradiated with light for 120 seconds to obtain a sheet having a thickness of 1 mm.
[0077] The volume percentage of the spherical silica particles in the resin composition of the obtained sheet was 40%.
[0078] The resulting sheet, 1 mm thick, was used to carry out a tensile test, and the resulting stress / strain curve is shown in Figure 2. The mechanical properties obtained from the stress / strain curves (tensile modulus, tensile stress at break, tensile strain at break, and tensile energy at break) are summarized in Table 1.
[0079] The platelet adhesion measurement and evaluation results are also shown in Table 1.
[0080] Comparative Example 1 A sheet was produced and evaluated in the same manner as in Example 1, except that the acrylate monomer (A) and silica particles were changed as shown in Table 1.
[0081] The resulting sheet was subjected to a tensile test, and the resulting stress / strain curve is shown in FIG.
[0082] The components (proportions) of the resin composition in Comparative Example 1, the volume percentage of the spherical silica particles in the resin composition, and the measurement and evaluation results of the mechanical properties (tensile modulus of elasticity, tensile stress at break, tensile strain at break, and tensile energy at break) and platelet adhesion of the obtained sheet are summarized in Table 1.
[0083] Examples 3 to 4 (Example 4: Reference Example) , Comparative Example 2 A sheet was produced and evaluated in the same manner as in Example 2, except that the acrylate monomer (A), the crosslinking agent (B), and the silica particles were changed as shown in Table 1.
[0084] A tensile test was carried out using the obtained sheet, and the stress / strain curves obtained are shown in FIG. 3 (Example 3), FIG. 4 (Example 4), and FIG. 6 (Comparative Example 2).
[0085] Table 1 summarizes the components (proportions) of the resin composition in each Example and Comparative Example, the volume percentage of the spherical silica particles in the resin composition, and the measurement and evaluation results of the mechanical properties (tensile modulus of elasticity, tensile stress at break, tensile strain at break, and tensile energy at break) and platelet adhesion of the obtained sheets.
[0086] Comparative Example 3 A sheet was produced in the same manner as in Example 2, except that the acrylate monomer (A) and silica particles were changed as shown in Table 1.
[0087] The obtained sheet had strong adhesion and poor strength, making it difficult to measure the mechanical properties. A solution was prepared by dissolving 400 parts by mass of the obtained sheet in 1600 parts by mass of methylene chloride, and the solution was applied to a PET film (Embret S-50) manufactured by Unitika Ltd. using a knife coater and air-dried to obtain a PET film having a resin composition coating. A platelet adhesion test was performed using the obtained PET film.
[0088] Table 1 below shows the components (proportions) of the resin composition in each Example and Comparative Example, the volume percentage of the spherical silica particles in the resin composition, and the measurement and evaluation results of the mechanical properties (tensile modulus, tensile stress at break, tensile strain at break, tensile energy at break) and platelet adhesion of the obtained sheets.
[0089] [Table 1]
[0090] As is clear from Table 1, the resin compositions obtained in Examples 1 to 4 had high tensile modulus at 0.05 to 0.25% elongation, high tensile stress at break and tensile strain at break, high tensile energy at break, and excellent mechanical properties such as high toughness. In addition, the platelet adhesiveness index was 0.3 or less, indicating that the material had excellent antithrombotic properties in which adhesion of platelets to the material surface was suppressed.
[0091] From the relative values of platelet adhesion in Examples 1 and 2 and Comparative Examples 1 and 2, it is seen that the platelet adhesion of the resin is not reduced by the inclusion of silica, which is a surprising result.
[0092] On the other hand, the resin composition of Comparative Example 1 did not contain silica particles, and therefore had low tensile modulus and tensile stress at break when elongated by 0.05 to 0.25%. The composition of Comparative Example 1, which did not contain silica particles, was not suitable for use as an elastomeric material.
[0093] The resin composition of Comparative Example 2 did not contain silica particles, and therefore had small tensile modulus at 0.05 to 0.25% elongation, tensile stress at break, tensile strain at break, and tensile energy at break, and was brittle. The composition of Comparative Example 2, which did not contain silica particles, was not suitable for use as an elastomeric material.
[0094] The resin composition of Comparative Example 3 did not contain silica particles or a crosslinking agent, and therefore the sheet was highly adhesive and had extremely poor material strength, making it impossible to obtain dumbbell test pieces for use in tensile testing.
Claims
1. A resin composition containing a polyacrylate resin and spherical silica particles, The polyacrylate resin comprises at least The following general formula (1): 【Chemistry 1】 [In formula (1), R 0 represents a methyl group; R 1 represents a hydrogen atom or a methyl group; and n represents an integer of 1 to 5. as a monomer unit, and the content of the spherical silica particles is in the range of 18 to 45 volume % of the total volume of the resin composition.
2. R 1 The resin composition according to claim 1 , wherein is a hydrogen atom.
3. The resin composition according to claim 1 or 2, further comprising a crosslinking agent.
4. An elastomer material comprising the resin composition according to any one of claims 1 to 3.
5. The elastomeric material of claim 4 having a tensile modulus of at least 400 kPa at an elongation of 0.05 to 0.25%.
6. 6. The elastomeric material of claim 4 or claim 5, exhibiting a tensile strain at break of at least 350%.
7. The elastomeric material according to any one of claims 4 to 6, exhibiting a tensile stress at break of at least 1000 kPa.
8. Tensile energy at break is at least 1500 kJ / m 3 The elastomeric material according to any one of claims 4 to 7, wherein
9. 9. The elastomeric material according to claim 4, which has a platelet adhesiveness index of 0.5 or less.
10. 10. The elastomeric material according to claim 4, having a platelet adhesiveness index of 0.3 or less.
11. A medical device comprising the elastomeric material according to any one of claims 4 to 10.
Citation Information
Patent Citations
JP1982500984A
Monomer inorganic colloidal sol impregnating agent and production thereof
JP1989115965A
Acrylic elastomer composition
JP1996109302A
Anti-fogging coating, anti-fogging molded article and anti-fogging sheet
JP2003206435A